747 IS 99MTC BONE SCINTIGRAPHY NECESSARY IN THE PREOPERATIVE WORKUP FOR PATIENTS WITH POTENTIALLY RESECTABLE ESOPHAGEAL SQUAMOUS CELL CANCER?. (17th September 2021) - Wei, Xiufeng; Li, Yin; Qin, Jianjun; Zhang, Ruixiang; Chen, Xiankai; Xie, Hounai; Xu, Lei; Yang, Yafan; Kang, Xiaozheng; Qi, Shu; Wang, Zhen
Abstract: : 99mTc bone scintigraphy(BS) is still the most widely used method to evaluate bone metastasis in China. The aim of this study was to investigate the necessity of the 99mTc bone scintigraphy in the preoperative workup for patients with potentially resectable esophageal squamous cell cancer (ESCC, cT1-4aN0–3). Methods: This was a prospective cross-section clinical trial (ChiCTR1800020304). There were a total of 471 patients who were diagnosed ESCC in Thoracic Surgery Clinic from October 2018 to September 2020. Of these 471 patients, 385 patients with cT1-4aN0–3 who were potentially candidates for surgical resection were consecutively enrolled into the study. BS was performed preoperatively. The treatment strategy could be changed if the bone metastasis was confirmed. The primary endpoint was the incidence rate of the treatment regimen being changed because of bone metastasis. The secondary endpoint was the rate of positive BS findings. Results: In all 385 patients, there are only 2(0.5%) patients changed their treatment regimen because of bone metastasis proved by BS. The rate of positive BS findings is 1%. The number of patients with false positive and false negative was 2(0.5%) and 2 (0.5%), respectively. The BS diagnostic performance for bone metastasis was as follows: sensitivity, 50%; specificity, 99.5%; positive predictive value, 50%; negative predictive value, 99.5% and accuracy, 99.0%. There were no significant difference of bone metastasis among the Age, Sex, Tumor location and Clinical stage. Conclusion: 99mTc bone scintigraphy is unnecessary in the preoperative workup for patients with potentially resectable esophageal squamous cell cancer.